Legal Status of Voluntary Human Shield in International Humanitarian Law - Homayon Habibi; Salehe Ramezani (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
International Humanitarian Law (IHL) as a series of rules which aims to protect civilians against the effects of hostilities has prohibited expressly the use of civilians as Human Shield. But voluntarism in human shield poses some question of law. In fact in some situations, civilians may put themselves in front of military objective by their will, which is a controversial issue. Some scholars consider the Voluntary Human Shield as taking direct participation in hostilities by civilians which deprives theme of the protections IHL grants to civilians. But the opponents view refuses this interpretation. This article rejects the idea of Voluntary Human Shield, as direct participant except in very specific situations where criteria of "direct participation" are met.